Organizational Readiness for Change to Lean Initiatives Amongst Nigerian Manufacturing SMEs: Literature Review and Questionnaire Pre-test - Mohammed, Inuwa; Suzari, Abdulrahim; Faruq Muhammad, Abubakar (INTI International University, 2023)
This study pre-tested measurements of organizational readiness for change from the dimensions of change efficacy and change commitment to measure manufacturing SMEs' confidence and willingness to change to lean. Expert opinion and respondents focus groups are used to examine the content of the items in the questionnaire, followed by pilot study of manufacturing SMEs, The result of the pilot study reveals the two dimensions of organizational readiness for change to Lean initiative; thus, change efficacy and change commitment have shown acceptable reliability. Change efficacy has a Cronbach Alpha of 0.911, while change commitment has 0.845 as Cronbach Alpha. The study concludes that the two dimensions of organizational readiness for change are reliable for conducting studies with large sample size.